(untitled) (Journal of Laboratory Animal Science, 2024)
The use of laboratory animals primarily rodents (mice) has increased over the past 20 years especially with the availability of transgenic and mutant strains. This increased use of mice along with novel research models with unique needs, has contributed to the evolution of the modern vivariums, decontamination equipment, imaging cores, ultra clean barriers, decontamination of feed and water etc. In addition, the industry has also made significant improvement in operating animal facilities. Automation of cage processing is just one example that signifies the sophistication which is an ongoing process. This sophistication and availability of better options not only improved animal welfare and ergonomics, but also efficiency in operating the modern animal facilities. As the animal facility operation involves several components, it could be challenging for an entry level manager to be knowledgeable about the best options that suits the needs of the facility. This article provides an overview of the most popular practices for the crucial aspects of animal care involving housing, animal health monitoring, feed and watering systems in addition to quality aspects. To provide a complete review of the laboratory animal facility operations and management would exceed the scope of this article. However, the topics discussed here are worthy of note when assessing the essential care and welfare of laboratory animals